2015
DOI: 10.1007/s10533-015-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

Salinization of coastal freshwater wetlands; effects of constant versus fluctuating salinity on sediment biogeochemistry

Abstract: Globally, coastal lowlands are becoming more saline by the combined effects of sea level rise, land subsidence and altered hydrological and climatic conditions. Although salinization is known to have a great influence on biogeochemical processes, literature shows contrasting effects that challenge the prediction of future effects. In addition, the effects of fluctuating salinity levels, a more realistic scenario than constant levels, on nutrient cycling in coastal wetland sediments have hardly been examined. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 53 publications
(60 reference statements)
5
42
0
Order By: Relevance
“…The strong inhibition of CH 4 production agrees well with previous results about how salinization affects methanogenic communities in natural freshwater wetlands (Baldwin et al, 2006; Chambers et al, 2011; van Dijk et al, 2015) and paddy soils (van der Gon and Neue, 1995). Overall, these studies also observed a negative correlation between salinity and methane production.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The strong inhibition of CH 4 production agrees well with previous results about how salinization affects methanogenic communities in natural freshwater wetlands (Baldwin et al, 2006; Chambers et al, 2011; van Dijk et al, 2015) and paddy soils (van der Gon and Neue, 1995). Overall, these studies also observed a negative correlation between salinity and methane production.…”
Section: Resultssupporting
confidence: 91%
“…This strong induction of AMT gene expression may be related to a highly increased bioavailability of ammonium upon the addition of NaCl to the paddy soil slurries. Due to cation exchange, the fast release of ammonium bound to soil particles is one of the geochemical key processes that occur in response to increasing salinity (Baldwin et al, 2006; van Dijk et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevailing paradigm has been that increased salinity leads to increased availability of P due to sulfide binding to Fe, leading to the release of P, and increasing mineralization of organically bound P. Increases in sediment P availability has been seen with increasing salinity in Chesapeake Bay (Hartzell and Jordan, 2012). However, other studies have reported decreased P availability with increasing salinity (Baldwin et al, 2006;van Dijk et al, 2015). Two plausible reasons we did not observe increased P in surface water are that increased plant uptake prevented the extra soil solution P from leaving the site in surface water, or that salt-induced flocculation of dissolved organic carbon immobilized P .…”
Section: Novel Biogeochemical Regimesmentioning
confidence: 99%
“…Climate change will cause rises in sea levels and increase the incidence of drought, both of which can contribute to increased salinisation, a major environmental factor limiting plant growth and productivity (Kenneth 1990;Arag€ u es et al 2015). Excessive accumulation of salt in soil imposes physiological constraints on plants, including osmotic stress, nutrient imbalance and disturbance to photosynthesis, thereby affecting plant growth (Parvaiz & Satyawati 2008;Chaves et al 2009;van Dijk et al 2015), and will alter plant stoichiometry, a key trait controlling nutrient cycling (Finn et al 2015;Zechmeister-Boltenstern et al 2015). Halophytes are remarkable in their ability to regulate their physiology to adapt to changes in saline conditions.…”
Section: Introductionmentioning
confidence: 99%